Transmural non-homogeneity of calcium-induced heart injury - Tribulová, N; Slezák, J; Ravingerová, T; Ziegelhöffer, A (Physiologia Bohemoslovaca, 1990)
The Ca paradox resulted in marked inhibition, up to disappearance, of histochemically studied enzyme activities (SDH, LDH, beta-HBDH, phosphorylase and ATPase) in the subepicardial layer of the myocardium. In the subendocardial region there was only a small decrease. These transmural differences correlated well with ultrastructural changes. It is assumed that the heterogeneity in transmural distribution of injury is the result of transmural differences in coronary flow.
Keywords: Animals; reperfuzní poškození; Female; Succinate Dehydrogenase; ženské pohlaví; fosforylasy; adenosintrifosfatasy; vápník; L-Lactate Dehydrogenase; Calcium; Male; Reperfusion Injury; L-laktátdehydrogenasa; krysa rodu Rattus; Hydroxybutyrate Dehydrogenase; Phosphorylases; zvířata; mužské pohlaví; Adenosine Triphosphatases; Myocardium; myokard; Rats; sukcinátdehydrogenasa; hydroxybutyrátdehydrogenasa